Implementation of Surah Al-Ma'un Learning Strategy to Increase Concern for Orphans at SD Negeri 105405 Sentang - Dahyar (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This study aims to Increase concern for orphans in Islamic Education Through Surah Al-Ma'un Learning Strategy. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests are used to improve students' abilities in developing a character of mutual respect and observation is used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that Learning Through Surah Al-Ma'un Learning Strategy can increase concern for orphans. This can be seen from the increase in the percentage of completeness of increasing students' abilities in developing a character of mutual respect in each cycle with details of the pre-cycle 45.54%, the first cycle 78.57% and in the second cycle increased to 89.57%. Thus, learning Through Surah Al-Ma'un Learning Strategy can be used as an alternative to improve student learning outcomes.